ANALISIS JEJAK KARBON PENGOLAHAN LIMBAH AIR SKALA PERKOTAAN DENGAN PENDEKATAN LIFE CYCLE ASSESSMENT (STUDI KASUS: IPAL X, JAKARTA SELATAN) - Ladiajanuarygusdi, Ayu Ramadhona; Syafila, Mindriany (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2025)
An increase in population often leads to a surge in the volume of wastewater that must be treated. Wastewater treatment plants (WWTPs) play a role in reducing environmental pollution caused by discharging wastewater into bodies of water. However, WWTPs are also a major source of greenhouse gas emissions, including carbon dioxide (CO₂), methane (CH₄), and nitrous oxide (N₂O). This study aims to evaluate the carbon footprint generated by treating 1 m³ of domestic wastewater at the IPAL X unit. The Life Cycle Assessment (LCA) approach with gate-to-gate system limitations was used. Data processing was done with the help of the OpenLCA software program. According to the LCA analysis results, the Moving Bed Biofilm Reactor (MBBR), Filtration, and Equalization Tank units produces the highest carbon footprint. The sourced of carbon footprint from electricity consumption and degrading organic compounds through biological treatment in MBBR unit.